Comprehensive Assessment of Orofacial Health and Disease Related Parameters in Adolescents with Juvenile Idiopathic Arthritis—A Cross-Sectional Study - Cordula Leonie Merle (Journal of Clinical Medicine, 2020)
Background: The aim of this cross-sectional study was to investigate oral health and functional status of adolescents with juvenile idiopathic arthritis (JIA) and its possible link to disease specific parameters. Methods: Patients with JIA were recruited (November 2012−October 2014) and disease specific information was extracted from patients’ records. Oral examination included: dental findings (decayed-, missing- and filled-teeth-index (dmf-t/DMF-T)), gingival inflammation (papilla-bleeding-index (PBI)) and periodontal screening index (PSI). Functional examination followed Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD). Additionally, modified Helkimo’s Clinical Dysfunction Index and radiographic scoring were recorded. Results: 59 JIA patients were included. The mean dmf-t/DMF-T was 2.6. Only one patient showed no signs of gingival inflammation, while 57.6% had a maximum PSI of 2 or less. Positive functional findings were assessed clinically in more than half of the patients. Major diagnosis by RDC/TMD was osteoarthrosis. Patients with at least one positive anamnestic or clinical functional finding revealed significantly higher radiographic scores (CI = 0.440, p = 0.022). Patients with increased c-reactive-protein had a significantly higher PBI (Z = −2.118, p = 0.034) and increased radiographic scores (CI = 0.408, p = 0.043). Conclusions: Adolescents suffering from JIA show high levels of caries experience and gingival inflammation. Temporomandibular joint dysfunction is often seen in JIA patients. Consequently, special dental care programs would be recommendable.